2008
DOI: 10.1186/1471-2288-8-63
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the international physical activity questionnaire in the Nord-Trøndelag health study (HUNT) population of men

Abstract: Background: There is no standardized method for the assessment of physical activity (PA). Therefore it is important to investigate the validity and comparability of different measures. The International Physical Activity Questionnaire (IPAQ) has been developed as an instrument for cross-national assessment of PA and has been validated in 12 countries. These instruments have acceptable measurement properties for monitoring population levels of PA among 18-65 yearold adults in diverse settings. However, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(197 citation statements)
references
References 24 publications
(39 reference statements)
14
170
3
6
Order By: Relevance
“…These correlations are comparable to results of other studies that have compared accelerometer-measured PA with questionnaires among various populations, including the IPAQ (Hagstromer et al, 2006;Hallal et al, 2010;Nicaise et al, 2011), IPAQshort version (Macfarlane et al, 2007;Kurtze et al, 2008), Global Physical Activity Questionnaire (Bull et al, 2009;Trinh et al, 2009), Epic Physical Activity Questionnaire (Cust et al, 2008), and Modifiable Physical Activity Questionnaire (Jacobi et al, 2009) (Coleman et al, 2012). Results showed that PA levels assessed by the PA questionnaires associated with the NHANES and BRFSS surveys were higher than the PA levels arising from the EVS.…”
Section: Validitysupporting
confidence: 85%
“…These correlations are comparable to results of other studies that have compared accelerometer-measured PA with questionnaires among various populations, including the IPAQ (Hagstromer et al, 2006;Hallal et al, 2010;Nicaise et al, 2011), IPAQshort version (Macfarlane et al, 2007;Kurtze et al, 2008), Global Physical Activity Questionnaire (Bull et al, 2009;Trinh et al, 2009), Epic Physical Activity Questionnaire (Cust et al, 2008), and Modifiable Physical Activity Questionnaire (Jacobi et al, 2009) (Coleman et al, 2012). Results showed that PA levels assessed by the PA questionnaires associated with the NHANES and BRFSS surveys were higher than the PA levels arising from the EVS.…”
Section: Validitysupporting
confidence: 85%
“…A total of 152 ESr values across five PA categories in IPAQ were retrieved (i.e. seventeen ESr from ten studies for walking (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) , seventeen ESr from twelve studies for MPA (16)(17)(18)(19)(20)(21)(22)(23)(24)26,27) , twenty-three ESr from ten studies for TMPA (21,24,25,(27)(28)(29)(30)(31)(32)(33) , thirty-five ESr from seventeen studies for VPA (16)(17)(18)(19)(20)(21)(22)(23)(24)(26)(27)(28)(29)(30)(31)(32)(33) and sixty ESr from sixteen studies for TPA (7,(17)…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While the International Physical Activity Questionnaire (IPAQ) showed relatively good validity in adults and adolescents aged 15-18 years, the correlations for children below that age were unsatisfactorily low (21,33,34) . The Children's Leisure Activities Study Survey (CLASS) was developed to assess PA behaviour in large-scale population studies and contains a list of thirty activities.…”
Section: Discussionmentioning
confidence: 99%